Colombian agricultural sector and armed conflict (2007 - 2022): An empirical analysis - Daniel Andrés Mosquera; Nadja Simone Menezes Nery de Oliveira; Pery Francisco Assis Shikida (Revista Brasileira de Estudos Regionais e Urbanos)
This article empirically proposes an unbalanced panel data model of random effects for the total of municipalities in Colombia in a period between 2007 and 2022 that analyzes the impact of the armed conflict on agricultural production, controlling by municipalities ZOMAC, post-peace agreement and sown area. The results show that production is negatively affected by 0.008% for each 1% additional victims of conflict in the municipalities each year; the analysis is carried out crop cycle, where transient crops are the most affected in the face of the conflict. On the other hand, the econometry model include the Differences-in-Differences parameter to estimate the post-agreements, between Colombian Estate and FARC, effect in the agriculture production. The results show that in a peace scenario, the agriculture production growth 0,07% each year.